Ballistic characteristics of 3D-printed auxetic honeycomb sandwich panel using CFRP face sheet. (June 2022) - Yan, Junbo; Liu, Yan; Yan, Zichen; Bai, Fan; Shi, Zhenqing; Si, Peng; Huang, Fenglei
Highlights: The ballistic impact effect and failure characteristics of AU honeycomb sandwich panel built with CFRP rear face sheet were experimentally investigated. The ballistic performance of AU honeycomb sandwich panel is compared with HEX honeycomb sandwich panels and AF honeycomb sandwich panels. Numerical results are in good agreement with experiments and can accurately describe damage mode. The effect of the face-sheet type and thicknesses and unit cell angle on the damage of AU honeycomb sandwich panels are numerically studied. Abstract: This work showed a numerical and experimental investigation examining the ballistic impact performance of auxetic honeycomb sandwich panels (AHSPs) built with a carbon fiber reinforced polymer (CFRP) bottom-sheet. At first, twelve honeycomb sandwich panels (HSPs) were analyzed under ballistic impact test conditions. The HSPs consisted of Q345 steel top-sheets, CFRP bottom-sheet, and a honeycomb aluminum core with three kinds of cell configurations (regular, reentrant, and enhanced reentrant hexagons, respectively). The performances of the HSPs were compared to a control set of Al foam-cored sandwich panels of identical areal densities. The results demonstrated that the auxetic honeycomb core improves the ballistic impact performance of HSPs by reducing the residual velocity and enhancing the damage tolerances. For the numerical research, the HSPs responses are deduced by finite element modeling. Parametric investigations were conducted to investigate the influences of the honeycomb type, unit cell angle and face-sheet type on the ballistic resistance of the HSPs. Numerical studies present that the ballistic limits and the HSP perforation energy are significantly influenced by the above factors. Graphical Abstract: Image, graphical abstract .